Arsenical C‐Glucoside Derivatives with Promising Antitumor Activity. Issue 21 (22nd June 2015) - D'Orazio, Giuseppe; Parisi, Gelsomina; Policano, Claudia; Mechelli, Rosella; Codacci Pisanelli, Giovanni; Pitaro, Michele; Ristori, Giovanni; Salvetti, Marco; Nicotra, Francesco; La Ferla, Barbara
Abstract: C ‐Glucoside derivatives covalently linked to the arsenic atom in different oxidation states have been synthesized by avoiding protection‐deprotection steps. While compound1, bearing an As V atom, did not show any significant biological activity, compound2, in which the glucose moiety is linked to the arsenic atom as dithioarsenical (As III ), showed promising antiproliferative activity on a cell line of neuroblastoma (SK‐N‐BE). Abstract : C ‐Glucoside derivatives covalently linked to the arsenic atom in different oxidation states have been synthesized. The C ‐glucoside conjugated to the phenyldithioarsolan group, showed promising antiproliferative activity on human neuroblastoma cells (SK‐N‐BE).